2016
DOI: 10.1016/j.jcrs.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of surface light scattering in intraocular lenses manufactured using an improved production process

Abstract: None of the authors has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Colin et al reported the formation of glistening in 86.5% of implanted AcrySof SN60WF IOLs, despite manufacturing changes (34). However, Miyata et al reported that the improved manufacturing process of AcrySof IOLs suppressed the development of surface light scattering up to 3 years postoperatively (35). It was proposed that other types of hydrophobic acrylic IOLs like enVista (manufactured by Bausch and Lomb) are glistening free clinically (36).…”
Section: Glisteningsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colin et al reported the formation of glistening in 86.5% of implanted AcrySof SN60WF IOLs, despite manufacturing changes (34). However, Miyata et al reported that the improved manufacturing process of AcrySof IOLs suppressed the development of surface light scattering up to 3 years postoperatively (35). It was proposed that other types of hydrophobic acrylic IOLs like enVista (manufactured by Bausch and Lomb) are glistening free clinically (36).…”
Section: Glisteningsmentioning
confidence: 99%
“…Matsushima et al reported that glistening and subsurface nanoglistenings caused decreased vision in 5 patients, leading to IOL explantation, which followed the improvement of visual acuity (12). However, the majority of the studies did not find a significant reduction of visual acuity caused by glistening or subsurface nanoglistening (1,16,34,35,(41)(42)(43). Xi with colleagues, reported that more severe glistening caused the reduction of contrast sensitivity at a high spatial frequency and visual field.…”
Section: Glisteningsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In order to reduce the occurrence of glistenings in AcrySof IOLs, Alcon Laboratories Inc. altered the manufacturing process in the early 2010s, implementing tight environmental and process controls in the formulation, cast moulding and curing operations. 37,38 Subsequently, Miyata et al 37 found that surface light scattering due sub-surface nanoglistenings was significantly reduced and Thomes and Callaghan 38 found that the percentage of IOLs with glistenings, induced in the laboratory, with a density of >100/mm 2 was 99% in the 2003 AcrySof IOL models and only 4.8% in AcrySof IOLs manufactured in 2012.…”
Section: Degradation/opacification/discolourations Within the Iolmentioning
confidence: 99%
“…Not only cataract extraction itself but also satisfactory postoperative refractive results are mandatory for good visual function. Moreover, artificial lens material has improved over time and complication rates have decreased [ 1 , 2 ]. Therefore, the expectations of patients undergoing cataract surgery are almost the same as those for refractive surgery, although preoperative astigmatism of more than 1.5 dioptres (D) is present in 20% of all cataract patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%